2005
DOI: 10.1007/s00467-004-1724-5
|View full text |Cite
|
Sign up to set email alerts
|

Extra corporeal membrane oxygenation and plasmapheresis for pulmonary hemorrhage in microscopic polyangiitis

Abstract: Early initiation of extracorporeal membrane oxygenation to treat acute hypoxemic respiratory failure secondary to massive pulmonary hemorrhage in microscopic polyangiitis in children can be life-saving while awaiting control of the autoimmune disease process by plasmapheresis and immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…A single case report exists of a patient with pulmonary hemorrhage in microscopic polyangiitis requiring ECMO support. TPE was performed in parallel with the ECMO circuit without adverse events or complications; the patient clinically improved and was eventually discharged [13]. None of these studies demonstrated safety and efficacy in patients post cardiac transplant; nor did they closely follow efficacy in reducing in HLA titers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A single case report exists of a patient with pulmonary hemorrhage in microscopic polyangiitis requiring ECMO support. TPE was performed in parallel with the ECMO circuit without adverse events or complications; the patient clinically improved and was eventually discharged [13]. None of these studies demonstrated safety and efficacy in patients post cardiac transplant; nor did they closely follow efficacy in reducing in HLA titers.…”
Section: Discussionmentioning
confidence: 95%
“…The procedures also pose clinical challenges with respect to maintenance of hemodynamic stability (with pressor support) and electrolyte levels. Although a few reports have been published on the use of TPE in tandem with hemodialysis [11,12], data is scarce on the safety, feasibility, and efficacy of performing TPE in parallel with ECMO [13]. In addition, the efficacy of TPE in parallel with ECMO in reducing anti-HLA antibodies or improving ventricular function has not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Our data point to the AP as the main contributor in the pathogenesis of oligoarticular JIA. Therefore, intraarticular complement activation is initiated predominantly by the AP [1]. The complement activation produces the proinflammatory protein C5a, which activates macrophages and T and B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Miller found an intraarticular deficiency of C3c and C3d in JIA [6]. Analysis of the peripheral blood (PB) suggested that activation of the alternative pathway (AP) of the complement system is the major contributor in the pathogenesis of JIA, culminating in the formation of the terminal membrane attack complex (MAC) and potentially leading to joint destruction [1,2,5]. A partial C4 deficiency and also elevation of C3 und C4 could be evaluated in JIA [4].…”
Section: Introductionmentioning
confidence: 98%
“…Extracorporeal membrane oxygenation has been used successfully in a few cases [48,49]. Hayes-Bradely [50 • ] suggested that prone position ventilation could improve oxygenation by better ventilation-perfusion matching and improved drainage of blood from the dorsal lung.…”
Section: Ventilationmentioning
confidence: 99%